Avaliação de diferentes solventes orgânicos utilizados na recuperação e purificação da torularodina da levedura Sporobolomyces ruberrimus - Kanno, Karen Yuri Feitosa (2018)
Carotenoids are molecules of commercial interest due to the coloration, are bioactive compounds, vitamin A precursors that have antioxidant, anticarcinogenic and anti-aging action. These pigments can be applied in the food, pharmaceutical, cosmetic and animal nutrition industry. There is a need for studies on microbial carotenoid recovery to refine the extraction and purification protocols, without the oxidative degradation of the molecule. This study aims at extracting, recovering and purifying of torularhodin produced by Sporobolomyces ruberrimus. For this purpose, the kinetic study of the growth and production of carotenoids in Erlenmeyers (n = 5) was carried out and the organic solvents, acetone, ethyl ether, petroleum ether and hexane, were evaluated for the recovery of carotenoids after mechanical extraction. The carotenoids were separated on preparative chromatography on the stationary phases containing silica, magnesium oxide, calcium carbonate and infusion soil. The growth kinetics obtained parameters of Xmax (18.8 g/L-1), µmax (0.071 h-1), YX/S (0.60 g.g1 ), YP/S (0.02 mg.g-1), YP/X (0.23 mg.g-1) and total carotenoids (3.84 mg.mL-1). The combination of acetone: hexane (1: 1 v/v) with glass beads resulted in 1.72 µg carotenoids.g cells-1 and 33% higher cell lysis over acetone: ethyl ether (1:1 v/v). The proportion of acetone: hexane (9: 1 v/v) showed a significant difference (p <0.05), resulting in the recovery of 2.22 µg carotenoids.g cells-1. The stationary phase containing silica was recovered 0.24 µg carotenoids.g cells-1. Analysis of the carotenoids and the product after extraction was performed on HPLC. In the crude extract, the presence of three carotenoids was observed and in the purified extract only one carotenoid, which confirms that the method used was efficient for the purification of the target biomolecule.